Effects of Hyperglycemia and Doxorubicin on Aging Induction Optimization: Focus on the Role of p53 and mTOR in Human Dermal Fibroblast Cells - Dimas Adhi Pradita; Achadiyani; Muhammad Hasan Bashari (International Journal of Science and Society, 2023)
Aging, a kind of physiological process, is influenced by a number of different biological and genetic factors, the driver for all age-related diseases. Aging of the skin can use samples of human fibroblasts (preputium) which are induced with high glucose media and doxorubicin using cell culture methods. Aging is measured using markers at the genetic level, namely p53 and mTOR. The p53 protein is one of the most important markers of apoptosis and the mTOR protein plays an important role in the proliferation, growth, motility, survival, autophagy of cell, including the synthesis of protein. Therefore, the optimization strategy of cell aging is well suited to physiological aging conditions In this review, we explore the optimization of aging in fibroblast cell cultures induced by high-glucose media and doxorubicin and review signs of aging, namely the biomarkers p53 and mTOR. The hope to be able to know aging is close to the original condition so that it becomes an opportunity as well as a challenge for the transition of basic research into developing interventions. Several major electronic databases, including Embase, PubMed, Cochrane, and CINAHL were used to select articles from the period between February 2013 and February 2023. From 5 available literatures, we demonstrated the activity of high-glucose media and doxorubicin as induction of fibroblast senescence. High-glucose media and doxorubicin showed an aging effect by increasing p53 and mTOR markers in fibroblast cell cultures. It is hoped that, with this article on aging optimization, insights into future research directions can be achieved.